Legal Protection of Parties Harmed by Non-Application of the Contradictoire Delimitatie Principle - Muhammad Adhyaksa Mansyur; Andi Suriyaman M. Pide; Muhammad Aswan (LEGAL BRIEF, 2022)
Land rights which are part of the earth as regulated in Law Number 5 of 1960 concerning Basic Agrarian Regulations Article 4 paragraph (1). Several factors cause land disputes such as:issue of 2 (two) or more land certificates on the same plot of land, which is known as overlapping. One of the land disputes is located in Maros Regency, with a decision number102/G/2016/PTUN. Mks. This dispute is based on Property Right Certificate No. 00795/Desa Baji Mangngai dated May 29, 1985 and issued 2 parts of the land parcels as a result of separation namely Certificate of Ownership No. 00811/Baji Mangngai Village and Ownership Certificate No. 00812/Desa Baji Mangngai and 1 part in 2011 namely Certificate of Ownership No. 00746/Baji Mangngai Village. The issuance of 2 or more land certificates is due to the non-implementation of the principle of contradictore delimatie based on Government Regulation no. 24 of 1997 concerning Land Registration.The type of research used is normative legal research with Statute Approach, Case Approach, and Conceptual Approach. The collection of legal materials was carried out using the library research method and the data obtained was analyzed qualitatively. The results of this study indicate thatIf the principle of contradictoire delimitatie is not applied consistently and consequently, it will certainly lead to legal uncertainty regarding land parcels. As a result, it will certainly affect the weak legal certainty of the object of the right to be used as a means for holders or owners of land rights. The dispute resolution steps that they or the BPN take are deliberations. Likewise in multiple certificate disputes, BPN also has the authority to negotiate, mediate and facilitate the parties to the dispute and initiate an agreement between the parties. However, if the problem cannot be resolved in the ways described above, then the disputing parties can make demands to the state administrative court.